On Pure Hyperradical in Semihypergroups - Kostaq Hila; Krisanthi Naka (International Journal of Mathematics and Mathematical Sciences)
This paper deals with a class of algebraic hyperstructures called semihypergroups, which are a generalization of semigroups. In this paper, we introduce pure hyperradical of a hyperideal in a semihypergroup with zero element. For this purpose, we define pure, semipure, and other related types of hyperideals and establish some of their basic properties in semihypergroups.